Experimental study of charging of dust grains in the presence of energetic electrons. (26th January 2022) - Paul, R; Sharma, G; Deka, K; Adhikari, S; Moulick, R; Kausik, S S; Saikia, B K
Abstract: The role of hot electrons in the charging of dust grains is investigated in a two temperature hydrogen plasma. A variety of dust particles are introduced into the system and secondary electron emission (SEE) from each of the dust types has been reported. A cylindrical Langmuir probe is used for determining the plasma parameters and a Faraday cup is connected to an electrometer in order to measure the dust current. The electrometer readings confirm the electron emission from the dust and SEE is observed from the tungsten dust in a low-pressure experimental plasma device for the first time.